SOSIALISASI PROGRAM PEMAJUAN KEBUDAYAAN KEMENTRIAN PENDIDIKAN DAN KEBUDAYAAN OLEH FAKULTAS ILMU BUDAYA UNMUL DI LEKAQ KIDAU, SEBULU: Socialization of The Ministry of Education and Culture Program for the Advancement of Culture by The Faculty of Cultural Sciences Unmul in Lekaq Kidau, Sebulu - Dahlan, Dahri; Max, Jonathan Irene Sartika Dewi; Setyowati, Ririn; Putra, Bayu Arsiadhi (Program Studi Sastra Indonesia Universitas Mulawarman, 2022)
Abstract: Socialization of The Ministry of Education and Culture Program for the Advancement of Culture by The Faculty of Cultural Sciences Unmul in Lekaq Kidau, Sebulu is a Community Service program implemented in 2022. This program was implemented by the Faculty of Cultural Sciences through a team that has been appointed, in collaboration with the relevant village government. In general, the service was carried out for 3x24 hours, but for the socialization as intended, it was carried out for 2x60 minutes at the village traditional lamin. The socialization was expected to be able to develop the potential and awareness of residents, especially activists and village governments to make the best use of the government's program. Welcomed and released by the government of Lekaq Kidau Village, Sebulu Sub-district, Kutai Kartanegara District the program has been successfully completed. Keywords: advancement of culture; community service; cultural village; Lekaq Kidau; socialization. Abstrak: Sosialisasi Program Pemajuan Kebudayaan Kementrian Pendidikan dan Kebudayaan Oleh Fakultas Ilmu Budaya Unmul di Lekaq Kidau, Sebulu adalah program Pengabdian Kepada Masyarakat yang dilaksanakan pada tahun 2022. Program ini dilaksanakan oleh Fakultas Ilmu Budaya melalui tim yang telah ditunjuk, bekerja sama dengan pemerintah desa terkait. Secara umum pengabdian dilaksanakan selama 3x24 jam, tetapi untuk sosialisasi sebagaimana yang dimaksud dilaksanakan selama 2x60 menit di lamin adat desa. Sosialisasi tersebut diharapkan dapat menumbuhkembangkan potensi dan kesadaran warga, terutama pegiat dan pemerintah desa untuk memanfaatkan program pemerintah tersebut dengan sebaik- baiknya. Disambut dan dilepas oleh pemerintah Desa Lekaq Kidau, Kecamatan Sebulu, Kabupaten Kutai Kartanegara, program tersebut telah selesai dengan baik. Kata kunci: desa budaya; pemajuan kebudayaan; pengabdian masyarakat; sosialisasi; Lekaq Kidau.